Chemoembolization of Hepatocellular Carcinoma - Lencioni, Riccardo; Petruzzi, Pasquale; Crocetti, Laura (Seminars in Interventional Radiology, 2013)
Transarterial chemoembolization (TACE) is the current standard of care for patients with intermediate-stage hepatocellular carcinoma (HCC) and relatively preserved liver function. In a meta-analysis of randomized controlled trials comparing conventional TACE regimens—including the administration of an anticancer-in-oil emulsion followed by embolic agents—versus best supportive care, TACE was shown to improve median survival from 16 to 20 months. Various strategies to improve outcomes for this patient group have become the subject of much ongoing clinical research. The introduction of an embolic drug-eluting bead (DEB) has been shown to substantially improve the pharmacokinetic profile of TACE, providing levels of consistency and repeatability not available with conventional regimens while concomitantly significantly diminishing systemic drug exposure. In randomized trials, DEB-TACE significantly reduced liver toxicity and drug-related adverse events compared with conventional TACE. In this article, technique, indications and contraindications, and clinical outcomes of conventional and DEB-TACE in the management of HCC are reviewed. In addition, scientific background and early clinical experience with the use of combination regimens including TACE and systemically active molecular-targeted agents with antiangiogenic properties are discussed. The combination of DEB-TACE and antiangiogenic therapy represents a potentially powerful approach that is currently undergoing clinical investigation in a phase 3 setting.
Keywords: chemoembolization; hepatocellular carcinoma; transcatheter therapy